Psychomentality in the dialogue of cultures: comparative analysis performance improvement psychomotor abilities of locomotion during the development of sports and recreation of East and West - Song, Peng; Mihuta, I.U. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose . Comparative analysis of the characteristics of development of the Eastern and Western health and fitness systems as basic assumptions preparedness dealing with specific aspects of motor activity. Material and methods. The study involved two groups ( 5 years experience of employment ) of 10 people each. Orientation training of the first group - improving the system of Tai Chi Chuan, the second - sports and health systems of the West. Results . Established a more positive activating effect of employment on the eastern systems of physical training on the central nervous system. In the first group there is a growing capability musculoskeletal system, the emergence of psychomotor functions, improving the accuracy of the final procedural and motor acts. Conclusions . Prolongation of study related aspects of psychomotor preparedness and spatio- temporal parameters of motor acts will reveal structural base optimization dialogue of cultures on the physical and spiritual development of man. While taking into account the direction, tools and techniques to achieve this goal.